Pengaruh Motivasi Terhadap Produktivitas Kerja Karyawan PT Indofood Sukses Makmur Tbk - Salim, Rizhfa Amalia Rahmadani; Sahila, Nasywania Risfa; Wahjono, Sentot Imam (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to determine the effect of Motivation on Employee Work Productivity at PT Indofood Sukses Makmur Tbk. The population in this study were employees of PT Indofood Sukses Makmur Tbk with a total of 60 respondents. The method of data collection in this study was using questionnaires, interviews, observations and documentation. The data analysis method used descriptive methods and quantitative methods, namely multiple Linear Regression analysis which was used to measure the effect of Motivation on Employee Work Productivity at PT Indofood Sukses Makmur Tbk. Based on the F test, the independent variable (Motivation) has a positive and significant effect on the dependent variable (Productivity). Through testing the correlation coefficient (r), it was obtained that the level of correlation or relationship between Motivation and Employee Work Productivity is a high relationship, namely 99.9% and Physical Needs are the most dominant variables influencing Employee Work Productivity at PT Indofood Sukses Makmur. Tbk.